166k views
1 vote
Simplify the fraction 4t^2-16 divided by 8 over t-2 divided by 6

User Bniwredyc
by
5.3k points

1 Answer

2 votes

For this case we must simplify the following expression:


\frac {\frac {4t ^ 2-16} {8}} {\frac {t-2} {6}} =

Applying double C we have:


\frac {6 (4t ^ 2-16)} {8 (t-2)} =

Simplifying:


\frac {3 (4t ^ 2-16)} {4 (t-2)} =

We take common factor 4 from the parentheses of the numerator:


\frac {3 * 4 (t ^ 2-4)} {4 (t-2)} =

We simplify:


\frac {3 (t ^ 2-4)} {(t-2)} =

We factor the numerator:


t ^ 2-4 = (t + 2) (t-2)

We rewrite the expression:


\frac {3 (t + 2) (t-2)} {(t-2)} =

We simplify:


3 (t + 2) =\\3t + 6

Answer:


3t + 6

User Jacobq
by
5.1k points